SOURCES OF RESPONSE BIAS IN COGNITIVE SELF-REPORT ITEMS: "WHICH MEMORY ARE YOU TALKING ABOUT?". (11th November 2018) - Hill, N; Mogle, J; Whitaker, E; Gilmore-Bykovskyi, A; Bhargava, S; Bhang, I; Sweeder, L; Van Haitsma, K
Abstract: Understanding how older adults interpret and respond to questions about cognition is critical to identifying response biases that may limit the accuracy of cognitive self-reports in identifying risk for cognitive decline. In this study, we used cognitive interviewing to identify features of cognitive self-report item content and structure that contribute to: 1) differing interpretations among respondents, and 2) older adults' decisional processes when responding. Older adults without dementia (n=49; Mage = 74.5 years; 36.7% male) completed an audio-recorded cognitive interview during which common cognitive self-report items were evaluated; the Question Appraisal System was used to analyze the resultant transcripts. The most common sources of response bias were vague item wording leading to multiple interpretations of meaning, incorrect assumptions regarding consistency of problems across situations, and provocation of an emotional reaction that influenced responses. Findings from this study identify modifiable sources of response bias to inform refinement of cognitive self-report measures.